Selfhood and 'Nostalgia': Sensory and Material Memories of the Childhood Home in Late Georgian Britain. (13th March 2019) - Begiato, Joanne
Abstract: Focusing on autobiographies written from the 1790s to the 1820s, this article demonstrates that material, emotional and sensory memories of the childhood house and its location were integral to constructions of self. First, it traces the interplay between prevailing cultural forms, family memory and identity, and proposes that these changed over time, shaped by cultural, social and economic factors. Second, in analysing these personal memories, it contributes to the debates around the meanings of the 'emotional disposition' of nostalgia, arguing that it was central to the formation of both national culture and individual selfhood.